Tingkat financial technology terhadap peningkatan kinerja UMKM dengan variabel intervening inklusi keuangan pada pelaku UMKM Kota Bengkulu - Sintia Safrianti; Veny Puspita; Seftya Dwi Shinta; Afriyeni Afriyeni (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
This study examines the effect of financial technology on improving the performance of Micro, Small and Medium Enterprises (MSMEs) with intervening variables of financial inclusion in MSMEs. Using data panels and PLS-SEM analysis. The samples were 90 MSMEs of Bengkulu City using the purposive sampling method. The data collection technique used is questionnaires. The results of this research on direct effect analysis found that financial technology affects the performance of MSMEs, financial technology affects financial inclusion, and financial technology has no effect on financial inclusion. In the indirect effect analysis, the results showed that financial inclusion does not intervene in the influence of financial technology on the performance of MSMEs.